(327) Long-Term Manpower planning research: estimates for cost of proposed Education plan for the period 1960-1985. (based on results of memo.no.325) بحث تخطيط القوى العاملة طويل الأمد: تقديرات تكلفة خطة التعليم المقترحة للفترة ١٩٦٠-١٩٨٥. (بناءً على نتائج المذكرة رقم ٣٢٥) - Rofail, Salib.; Hamdy, Mostafa.; Khalil, Mahmoud. (INP, 2018)
This study aims to estimate the cost of developing educational facilities as outlined in Memo No. (325), serving as a test of the feasibility of implementing the proposed education plan. The estimates also provide a foundation for projecting necessary changes in the education budget. The study examines the evolution of the ratio of education expenditure to national income during the period 1955/56 to 1960/61. The provided table shows that education spending averaged around 4% of national income and 19% of the state budget throughout the period. This relative consistency in expenditure reflects the government's prioritization of education. These indicators serve as a basis for more accurate forecasting of future educational financing within broader national plans.